PENGARUH VARIAN PRODUK DAN SOSIAL MEDIA INSTAGRAM TERHADAP KEPUTUSAN PEMBELIAN DI KEDAI TEMAN CERITA TENTE - Atika Apriana; Sri Ernawati (JURNAL ILMIAH NUSANTARA, 2024)
A purchasing decision is a final decision that a consumer has to purchase a good or service with various certain considerations. This research aims to determine the influence of product variants and Instagram social media on purchasing decisions at Kedai Teman Berita Tente. The results of this research show that product variants do not have a significant effect on purchasing decisions, while Instagram social media has a significant effect on purchasing decisions.